2013
DOI: 10.1152/jn.00010.2013
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of HCN subunits alters voltage-dependent gating of h-channels in CA1 pyramidal neurons from dorsal and ventral hippocampus

Abstract: expression of HCN subunits alters voltage-dependent gating of h-channels in CA1 pyramidal neurons from dorsal and ventral hippocampus. J Neurophysiol 109: 1940 -1953, 2013. First published January 16, 2013 doi:10.1152/jn.00010.2013The rodent hippocampus can be divided into dorsal (DHC) and ventral (VHC) domains on the basis of behavioral, anatomical, and biochemical differences. Recently, we reported that CA1 pyramidal neurons from the VHC were intrinsically more excitable than DHC neurons, but the specific i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
111
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(123 citation statements)
references
References 46 publications
12
111
0
Order By: Relevance
“…These could be due to an increase in the HCN1 channel current as evidenced by voltage clamp recording and a higher level of HCN1 mRNA expression in neurons from Aβ-treated rats. It has been reported that pyramidal neurons with more depolarized membrane potential and higher Rin have a much higher density of Ih channels (Dougherty et al, 2013). On the other hand, as R in inversely correlates with the cell diameter, this change in the passive membrane properties is consistent with a significant reduction in the soma diameters of these neurons in the present model of AD.…”
Section: Alterations In the Intrinsic Electrophysiological Characterisupporting
confidence: 82%
See 1 more Smart Citation
“…These could be due to an increase in the HCN1 channel current as evidenced by voltage clamp recording and a higher level of HCN1 mRNA expression in neurons from Aβ-treated rats. It has been reported that pyramidal neurons with more depolarized membrane potential and higher Rin have a much higher density of Ih channels (Dougherty et al, 2013). On the other hand, as R in inversely correlates with the cell diameter, this change in the passive membrane properties is consistent with a significant reduction in the soma diameters of these neurons in the present model of AD.…”
Section: Alterations In the Intrinsic Electrophysiological Characterisupporting
confidence: 82%
“…It did not Changes in the intrinsic active membrane properties of pyramidal neurons were further assessed by examining the neuronal responses to depolarizing and hyperpolarizing currents. 16 The sag voltage which reflects the activation of Ih channel was also measured at the soma membrane of CA1 pyramidal neurons in response to hyperpolarizing injected currents (Figs. 4A & B).…”
Section: Resultsmentioning
confidence: 99%
“…The expression profiles of genes encoding adhesion molecules and ion channels 32,43 may determine intrinsic electrophysiological properties of discrete hippocampal neuronal populations, such as the differences in neuronal excitability 45 and synaptic plasticity [46][47] that have been detected along the long axis. For example, hyperpolarisation-activated cation channels HCN1 and HCN2, which mediate hyperpolarization-activated currents (I h ) currents, exhibit dorsoventral expression differences 48 and are important for a spatial function that is dorsoventrally graded [49][50][51] . In general, neurotransmitter receptor expression varies across the long axis for the majority of transmitter systems (Supplementary Table 1).…”
Section: Gene Expression Along the Long Axismentioning
confidence: 99%
“…Such PKC-induced modulation of I h in somatosensory neurons might - if present - link the IFN signaling to neuronal excitability changes [7]. Notably, biophysical characteristics of HCN1 channels expressed in HEK293 cells (in particular their V 1/2 ) are closely related to neuronal HCN channels when recorded at dendrites of pyramidal cortical and hippocampal neurons in cell attached mode [9,27,28]. This apparent phenomenological resemblance might specify HEK293 or N1E-115 cells as model systems to further elucidate neuronal mechanisms of PKC actions.…”
Section: Discussionmentioning
confidence: 99%